Determination of hydraulic retention time using a Piecewise linear regression analysis in the anaerobic digestion process. Issue 11 (3rd June 2019) - Jo, Hyeonsoo; Choi, Jangwook; Muhammad, Ishfaq; Akhtar, Muhammad Usman; Li, Xiang; Bao, Jun; Choi, Shinmook; Ali Shah, Syed Waqas; Qayum, Abdul; Altaf Hussain, Muhammad; Lee, Jaehee
ABSTRACT: Hydraulic retention time (HRT) determination in the anaerobic digestion process is an important factor for reactor design. This study aims to investigate the optimal HRT determination method for beef manure and sawdust mixture in the anaerobic digestion (AD). The Piecewise linear regression (PLR) analysis method was applied to compare the HRT with MGTP95 determined by the Modified Gompertz model analysis, cumulative methane yield (Cum.CH4 ), cumulative biomass removal (Cum.BMR) and biodegraded volatile solids (PLTBVS ). Lab-scale (6 cases of lab-scale in the anaerobic digestion) experiments were performed and analyzed by Modified Gompertz model and Piecewise linear regression analysis. The parameters selected for Piecewise linear regression analysis: Cumulative methane yield (PLTCUM.CH4), cumulative biomass removal (PLTCUM.BMR), biodegradable volatile solids (PLTBVS) and time to produce 95% of methane yield potential from Modified Gompertz model (MGTP95). The HRT determined from PLTCum.CH4 varied in between 26.4~34.9 days, and which were 0.4~3.9 days, 8.3~16.0 days, and 9.4~22.2 days shorter than PLTCum.BMR, MGTP95,   and PLTBVS, respectively. The daily maximum methane yield rate in the HRT from PLTCum.CH4 showing the highest daily methane yields rate which was less than 2.1%. Therefore, reactor utilization rate and organic loading rate for PLTCum. BMR, MGTP95, and PLTBVS were 94.4~99.4%, 78.0~84.4%, and 70.9~83.9%, respectively, lower than PLTCum.CH4. Conclusively, the HRT from PLTCum.CH4 is the most appropriate method to maximize the organic loading rate relative to other determination methods.